The Effectiveness of Using Wordwall in Indonesian Language Learning on Advertisements, Slogans, and Posters at SMPN 4 Kota Cirebon - Ayu Salsabila, Wanda; Hesti Muliawati; Ilmiyanti Rahayu Putri; Astriyani (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to investigate the effectiveness of using Wordwall inteaching Indonesian language, specifically on the topics ofadvertisements, slogans, and posters at SMPN 4 Kota Cirebon. Theresearch subjects were students of SMPN 4 Kota Cirebon, totaling 52participants, selected through purposive sampling. This qualitativestudy employed a descriptive method. Data were collected usingquestionnaires and observations. The data analysis process consistedof three stages: data reduction, data presentation, and conclusiondrawing. The findings indicate that the use of Wordwall is effectivein enhancing various aspects of the learning process. It increasesstudent engagement and understanding of the material, aligns wellwith learning objectives, boosts motivation, encourages collaborationand healthy competition, improves time efficiency, enhances studentfocus, and creates a more effective and conducive learningenvironment.